Identifikasi Kenyamanan Kota Tanjungpinang Berdasarkan Indeks Panas Humidex - Diana Cahaya Siregar; Vivi Putrima Ardah; Regina Dara Ninggar (School of Postgraduate Studies, Diponegoro Univer, 2019)
The development of Tanjungpinang City in several sectors is an effort to make that city more advance. However, there is an important problem that needs to be considered. It is the problem of the comfort life index for the population who are living in Tanjungpinang City. The climate change can affect physiological comfort in an area. The increasing of temperature can trigger the Urban Heat Island. The aim of this study is to know the comfort life index in Tanjungpinang City using a heat index called as Humidex. The data are the air temperature, air humidity, and surface wind speed for the period of 1989-2018 from the Tanjungpinang Meteorological Station. The comparison of Humidex to wind speed and the number of vehicles in Tanjungpinang City was calculated to determine the effect on the heat index in Tanjungpinang City. The results show that the Humidex monthly average in the Tanjungpinang City area ranged from 32.6 to 34.0 °C. The highest Humidex monthly average is in May and June, and the lowest value is in January. The tendency of increasing Humidex ranged from 0.08 to 0.9 °C and decreasing ranged from 0.07 to 0.8 oC with the determinant coefficient value is 0.55. The increasing of wind speed impacts to decrease the value of Humidex. The increasing of the number of vehicles periodically impacts to increase the value of Humidex exponentially. There is an increasing of the thermal comfort when there is a decreasing value of Humidex or vice versa.